Hermetic storage technologies preserve maize seed quality and minimize grain quality loss in smallholder farming systems in Mexico - Odjo, Sylvanus; Palacios Rojas, Natalia; Burgueño, Juan; Corrado, Marina; Ortner, Tim; Verhulst, Nele (Elsevier, 2022)
Reducing maize postharvest storage losses is a challenge for millions of smallholder farmers in Mexico. A previous study documented the effects of storage technologies on stored grain losses. The current study follows up on those experiments to evaluate the effectiveness of diverse storage technologies — polypropylene bags with and/or without insecticide, hermetic metal silos, hermetic bags, recycled plastic containers, silage plastic bags, micronized lime, and standard lime — in maintaining grain and seed quality during 2017 and 2018 at six sites: three agroecologies below 500 m above sea level (masl) and three agroecologies above 2000 masl. Maize samples stored using each of the above technologies were collected before and after six months of storage. Pest-free samples were analyzed for grain composition (starch, protein, oil, ether extracts, polyphenols contents), selected physicochemical parameters (fat acidity, an indicator of biochemical changes during storage; hundred kernel weight; flotation index, an indirect parameter of grain density; color; and germination. Storage technologies did significantly affect macronutrient content, but the quality of grain stored under non-hermetic conditions was reduced, as reflected in significantly increased fat acidity and flotation index. Seed germination was less affected by the type of storage technology at sites above 2000 masl but a significant effect was observed at sites below 500 masl. On average, the germination capacity of seed stored using non-hermetic technologies (polypropylene bags with or without insecticide or lime) dropped 56% at lowland sites, as compared to 2.8% for seed stored using hermetic metal silos or hermetic bags. Airtight technologies also minimized quality losses by reducing metabolic activities. By limiting insect and fungi infestation and reducing quantity and quality degradation in stored maize, hermetic technologies can contribute to Mexican smallholder farmers' food security.